Effects of polystyrene microplastics on the growth and metabolism of highland barley seedlings based on LC-MS - Xiao, Wenqi; Xiang, Peng; Liao, Wenlong; Xiong, Zhuang; Peng, Lianxin; Zou, Liang; Liu, Bingliang; Li, Qiang (Frontiers in Plant Science, 2024)
Microplastics are widely present in the environment and can adversely affect plants. In this paper, the effects of different concentrations of microplastics on physiological indices and metabolites of highland barley were investigated for the first time using a metabolomics approach, and revealed the response mechanism of barley seedlings to polystyrene microplastics (PS-MPs) was revealed. The results showed that the aboveground biomass of highland barley exposed to low (10 mg/L) and medium (50 mg/L) concentrations of PS-MPs increased by 32.2% and 48.2%, respectively. The root length also increased by 16.4% and 21.6%, respectively. However, the aboveground biomass of highland barley exposed to high (100 mg/L) concentrations of PS-MPs decreased by 34.8%, leaf length by 20.7%, and root length by 25.9%. Microplastic exposure increased the levels of antioxidant activity, suggesting that highland barley responds to microplastic stress through oxidative stress. Metabolome analysis revealed that the contents of 4 metabolites increased significantly with increasing PS-MPs concentration in positive ionmode, while the contents of 8 metabolites increased significantly with increasing PS-MPs concentration in negative ionmode (P < 0.05), including prunin, dactylorhin E, and schisantherin B. Additionally, PS-MPs significantly interfered with highland barley flavonoid biosynthesis, pyrimidine metabolism, purine metabolism, fatty acid biosynthesis, and phenylpropanoid biosynthesis metabolic pathways. This study provides a new theoretical basis for a deeper understanding of the effects of different concentrations of PS-MPs on highland barley.